The look, listening and the act of writing as a methodological process of research in arts (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article is the result of the classes taught in the discipline Acts of Scripture for master's students in the Graduate Program in Arts PPGARTES-UFPA, in 2021. It aims to reflect on the methodological processes of research in the field of arts and its multiple languages, proposing deepening on the acts of looking, listening and writing as research techniques necessary for the investigation of creative processes, whose emphasis is on dialogical actions between subjectivities and intersubjectivities of the subjects involved in the process. The epistemological basis used as a guiding thread in the construction of the article is based on authors of ethnography (Geertz, 2008; Oliveira, 2000; Peixoto, 1999), Phenomenology (Merleau-Ponty, 2003; Rangel, 2009; Salles, 1998) and Cartography (Deleuze, 1992, 1997, 1997;  Foucault, 2004, 1997; Martin-Barbero, 2002), in addition to other authors who assist in the reflection.
Keywords: Look; Listen; Write; Research in arts